Teacher Instructional Communication in Offline Learning Post Pandemic at SMK KP Paseh - Dian Mulyani; Dedeh Fardiah; Dede Lilis Chaerowati (Didaktika: Jurnal Kependidikan, 2024)
This study is driven by the shift from online to offline learning following the COVID-19 pandemic, which has had a negative impact on students' psychological, emotional, and cognitive aspects. The aim of this research is to analyze teachers' instructional communication in face-to-face learning through the lens of cognitive learning theory. The research methodology is a descriptive qualitative approach with a case study design and a constructivist paradigm. The primary informants include teachers and school principals, while secondary informants consist of public relations officers and students, selected through purposive sampling. Data was gathered through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing, with validation through source triangulation. The findings revealed that teachers at SMK KP Paseh meticulously planned learning activities post-pandemic, considering students' needs and appropriate teaching strategies. Evaluations were more structured, and instructional communication was aligned with these plans, focusing on creating an engaging and effective learning environment.